Evaluation the Effect of different Cooling Cycles on the Hardness Surface of the Conventional Feldspathic Zirconia - Shahad Hazim Ali; Lateef Essa Alwan; Abdul Kareem J. Al-Azzawi (Journal of Techniques)
Cooling rate is the main fact in success and life span of all ceramic restoration through its effect on mechanical properties and producing a residual tensile stress, crack propagation and failure restorations. The goals of this study is to assess the impact of diverse cooling cycles (slow cooling – fast cooling) on the surface hardness of the Zirconia (VM9). A total of 30 conventional Y-TZP Zirconia (Vita VM9) disks were fabricated according manufacturers recommendation. The samples were partition into three categories depending on the cooling system. Each group consisted of ten specimens in diameter (2mm×10mm). Control group: samples are unescorted by any change. Fast cooling group: these specimens were fast cooled after second firing (910C0 -600C0) with opening Oven muffle 25% withholding time for 5 minute and remove from the furnace to cool at room temperature. Slow cooling group: specimens were slow cooled after second firing (910C0 -400C0) with opening Oven muffle 25% withholding time for 5 minute and remove from the furnace to cool at room temperature. Each specimen was subjected to hardness test in load 9.8N at 15s using Digital microvickers Hardness tester, Scanning electron microscope. The statistical analysis revealed that, the highest vickers hardness mean value was for the control group (690.57 ± 69.9563) and for second group (618.12± 53.6164) and for third group (631.75±65.3858), The facts were statistically examined by applying ANOVA test (P- value) testes which revealed significant differences(p=0.038) (p<0.05) among groups. Conclusion: The impact of cooling cycle on the hardness surface measurements of the Zirconia (Vita VM9) between the three groups was significant. The slow cooling shows a higher value of (VH) Hardness and recommended for Zirconia than the fast cooling.